THE INFLUENCE OF FLASHCARD MEDIA THROUGH THE TRACKING GAME ON THE LITERACY AND SOCIAL INTERACTION ABILITIES OF EARLY CHILDREN AGED 4-5 YEARS - Saida Ahmad; Nurbiana Dhienie; R Sri Martini Meilanie (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the effect of using flashcards through a search-and-find game on the literacy and social interaction skills of 4–5-year-old children. This research is motivated by the low level of early literacy skills in children, particularly in recognizing letters, sounds, and simple vocabulary, as well as the suboptimal social interaction of children in learning activities. Furthermore, the learning process tends to be teacher-centered and underutilizes engaging and contextual educational media and games. This study used a quantitative approach with an experimental method. The research design used was an experiment with two independent variables, namely flashcard media and a tracking game, and two dependent variables, namely children's literacy skills and social interactions. The subjects of the study were children aged 4–5 years at Pembina 1 State Kindergarten, North Cikarang District. Data collection techniques were carried out through observation using instruments compiled based on early childhood development indicators. The data were analyzed using statistical analysis techniques to test the influence of each variable and the interaction between variables. The results of the study showed that: (1) there was an influence of the use of flashcard media on the literacy skills of early childhood children, (2) there was an influence of the use of flashcard media on children's social interactions, (3) there was an influence of the trace-finding game on children's literacy skills, (4) there was an influence of the trace-finding game on children's social interactions, and (5) there was an influence between the use of flashcard media and the trace-finding game in improving the literacy skills and social interactions of early childhood children. Thus, the use of flashcards combined with a tracking game has proven effective in improving literacy and social interaction skills in early childhood. This research is expected to serve as a reference for teachers in developing more innovative, interactive, and child-centered learning.